Basal cell skin cancer with metastasis to subcutaneous fat—a case report - Rumyantseva, Veronika; Sukhotko, Anna; Sukharev, Victor; Bumbu, Anna; Zakurdaev, Evghenii; Covantsev, Serghei (Frontiers in Surgery, 2025)
Basal cell carcinoma (BCC) is a malignant neoplasm of the skin that originates from the cells of the basal layer of the epidermis and is the most common skin cancer worldwide, accounting for more than 75% of all nonmelanoma skin cancers. About 4 million BCCs are diagnosed annually worldwide. Despite being the most common skin tumor, metastasis is rare and occurs in 0.0028%–0.55% of cases. In this case report, we present a rare case of giant basal cell carcinoma with metastasis to the subcutaneous fat in a 69-year-old woman.